2013
DOI: 10.1088/0031-8949/2013/t156/014008
|View full text |Cite
|
Sign up to set email alerts
|

Low charge states of Si and S in Cygnus X-1

Abstract: Strong, relatively short, absorption dips have been observed in the x-ray light curves measured from the high mass x-ray binary system Cygnus X-1. With increasing strength of the dips, which are believed to be caused by 'clumps' of cold material present in the stellar wind of Cyg X-1's companion star, K-shell absorption lines in L-shell ions of Si and S develop. To determine the bulk motion of the clumps via the Doppler shifts of these lines with high accuracy, we measured their reference energies using the La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…This is more consistent with the picture of photons being reprocessed by clumps of material with an onion-like structure, where the outer layers shield the colder and denser core of the clump from the ionizing radiation of the compact object. Similar results were also obtained for Cyg X-1 (Hell et al 2013), where these lines are seen in absorption.…”
Section: Center Of Line Blendssupporting
confidence: 86%
See 1 more Smart Citation
“…This is more consistent with the picture of photons being reprocessed by clumps of material with an onion-like structure, where the outer layers shield the colder and denser core of the clump from the ionizing radiation of the compact object. Similar results were also obtained for Cyg X-1 (Hell et al 2013), where these lines are seen in absorption.…”
Section: Center Of Line Blendssupporting
confidence: 86%
“…Watanabe et al (2006) build a three-dimensional Monte-Carlo radiative transfer model and report a mass loss rate for the companion star and the structure of the wind, although they do not analyze the line emission from the L-shell silicon ions, but only from H-like Si. In the case of Cygnus X-1, the Kα absorption features in L-and K-shell ions of silicon and sulfur have been measured and used to diagnose the nature of the stellar wind (Hanke et al 2008;Hell et al 2013;Miškovičová et al 2016). Specifically, these features have been shown to be produced by "clumps" of onion-structured material, where the inner layers are colder, denser, and less ionized, moving in and out of the observational line of sight.…”
Section: Introductionmentioning
confidence: 99%
“…As HDE 226868 fills > ∼ 90% of its Roche lobe (Gies et al 2003) and has a strong (a few 10 −6 M yr −1 , Gies et al 2003) fast wind, the black hole accretes via a focussed wind (Friend & Castor 1982;Gies & Bolton 1986a,b;Sowers et al 1998;Miller et al 2005;Hanke et al 2009;Hell et al 2013;Miškovičová et al 2015, and others). Values for ∞ for HDE 226868 vary in the literature: Davis & Hartmann (1983) obtain (2300±400) km s −1 in the hard state, but Vrtilek et al (2008) find 1420 km s −1 in the soft state.…”
Section: Introductionmentioning
confidence: 96%
“…Holczer et al (2010) reported Si vi to Si xiv absorption lines in the slow warm absorber of bright Seyfert 1 galaxy MCG 6-30-15. Hell et al (2013) observed the K-shell absorption lines from Si viii to Si xiv in the high-mass X-ray binary Cygnus X-1. More recently, Si viii to Si xiv K lines have been detected in warm absorbers around the quasar MR 2251-178 (Reeves et al2013).…”
Section: Introductionmentioning
confidence: 99%